Vaccines and Senior Travellers - Ecarnot, Fiona; Maggi, Stefania; Michel, Jean-Pierre; Veronese, Nicola; Rossanese, Andrea (Frontiers in Aging, 2021)
Background: International tourist travel has been increasingly steadily in recent years, and looks set to reach unprecedented levels in the coming decades. Among these travellers, an increasing proportion is aged over 60 years, and is healthy and wealthy enough to be able to travel. However, senior travellers have specific risks linked to their age, health and travel patterns, as compared to their younger counterparts. Methods: We review here the risk of major vaccine-preventable travel-associated infectious diseases, and forms and efficacy of vaccination for these diseases. Results: Routine vaccinations are recommended for older persons, regardless of whether they travel or not (e.g., influenza, pneumococcal vaccines). Older individuals should be advised about the vaccines that are recommended for their age group in the framework of the national vaccination schedule. Travel-specific vaccines must be discussed in detail on a case-by-case basis, and the risk associated with the vaccine should be carefully weighed against the risk of contracting the disease during travel. Travel-specific vaccines reviewed here include yellow fever, hepatitis, meningococcal meningitis, typhoid fever, cholera, poliomyelitis, rabies, Japanese encephalitis, tick-borne encephalitis and dengue. Conclusion: The number of older people who have the good health and financial resources to travel is rising dramatically. Older travellers should be advised appropriately about routine and travel-specific vaccines, taking into account the destination, duration and purpose of the trip, the activities planned, the type of accommodation, as well as patient-specific characteristics, such as health status and current medications.